Effect of Silver Nanoparticles of Herbal Origin on the Compressive and Push-out Bond Strengths of Mineral Trioxide Aggregate - Samiei, Mohammad; Adibkia, Khosro; Ghasemi, Negin; Tupal , Ayda; Mohaghegh, Seraj (Iranian Endodontic Journal, 2023)
Introduction: The purpose of this in vitro study was to investigate the effect of incorporating silver nanoparticles (AgNPs) of herbal origin into mineral trioxide aggregate (MTA) on the push-out bond strength (PBS) and compressive strength (CS) in simulated furcal area perforations. Materials and Methods: In this in vitro study, simulated furcal area perforations (1.3 mm in diameter and 2 mm in depth) were created in 40 extracted human lower molar teeth, which were divided into two groups (n=20): MTA alone and MTA combined with AgNPs (2% wt). Using a universal testing machine, PBS was evaluated by performing push-out tests, while CS was assessed using cylindrical specimens. The normal distribution of data was checked using the Kolmogorov-Smirnov test, and statistical analysis was performed using two-way ANOVA. Results: The CS results showed no significant difference between the MTA group at 4 and 21 days (P=0.297), but a significant difference was observed in the nanosilver/MTA group (P=0.013). However, there was no significant difference in the push-out bond strength among the study groups (P>0.05). Conclusion: The incorporation of herbal origin silver nanoparticles did not significantly affect the PBS or CS of MTA.